Perlakuan Akuntansi atas Pengakuan Pendapatan pada PT “X” di Surabaya - Diana Zuhroh; Tjandra Wasesa; Wiratna W; Sutini Sutini; Heri Toni (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This research aims to determine the accounting treatment of revenue recognition at PT "X". The research method used is descriptive qualitative, with research limitations namely the recognition of PT "X"'s income for two months, period January - February 2023. PT "X" has a foreign language course service business which is domiciled in Surabaya and has four foreign language course program packages, namely regular, prime and private focus classes. For the four course programs, the payment system is all done by paying in advance before the course begins and the class ends in two to four months. The research results show that PT "X" records and recognizes all payment receipts as income in the same period or month as the basis for preparing monthly profit and loss reports. This results in the income value contained in the monthly profit/loss report not reflecting its fair value.